Analysis of Chemosensory Genes in Full and Hungry Adults of Arma chinensis (Pentatomidae) Through Antennal Transcriptome - Shaolong Wu; Shaolong Wu; Wan Deng; Mi Li; Yansong Xiao; Jiaying Li; Kai Teng; Zhipeng Xiao; Xiaohong Li; Zhicheng Zhou; Youzhi Li (Frontiers in Physiology, 2020)
The predatory insect Arma chinensis (Hemiptera: Pentatomidae) is widely distributed in China, where it is also used to control many agricultural and forest pests. The chemosensory genes expressed in its antennae play crucial roles in food-seeking and mating behaviors. To better understand the olfaction of A. chinensis antennae, we identified the genes related to food-seeking and mating. Sequencing of the antennal transcriptomes of full and hungry male and female A. chinensis revealed 38 odorant-binding proteins (OBPs), 1 chemosensory protein (CSP), 1 Niemann–Pick C2 protein (NPC2), 3 odorant receptors (ORs), 12 ionotropic receptors (IRs), 2 gustatory receptors (GRs), and 3 sensory neuron membrane proteins (SNMPs). These results were used to construct phylogenetic trees. A quantitative real-time PCR (qRT-PCR) analysis showed that the relative transcript levels of AchiGR1, AchiGR2, and AchiOBP28 were higher in female than in male antennae in both full and hungry insects, but that the expression of AchiOBP13 and AchiOBP16 was higher only in full A. chinensis females. Thus, the latter genes may encode proteins involved in oviposition selection behavior. AchiGRs (1 and 2), AchiIR6, and AchiOBPs (6–8, 12, 20–22, 28, and 34) were highly expressed only in the antennae of full males, indicating the participation of these genes in mate-searching or male pheromone recognition. The expression of AchiOBP31 in the antennae of starved males, AchiOBPs (15, 18, and 29) in the antennae of starved females, and AchiOBPs (3, 4, and 24) in the antennae of starved males and females suggested that these genes encode food-seeking functions. Our identification of chemosensory genes in A. chinensis antennae and their differential expression in full and hungry insects provides the basis for further functional studies on the chemoreception system of A. chinensis and the sex hormones of predatory insects.